PENGARUH STRUKTUR AKTIVA, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP STRUKTUR MODAL PERUSAHAAN YANG TERDAFTAR DI BEI PADA TAHUN 2009-2016 - Okta vianti; Lukman Gustian (EQUILIBIRIA, 2019)
This research aims to provide empirical evidence for the company and investors in the form of information that is important to know the influence of the structure of assets, profitability, and the growth company against the capital structure of the company. This research is a quantitative type because in it refers to the calculation of research data in the form of numbers. The variables of this study include dependent and independent variables. The sample in this research is cement company that listed in Indonesia Stock Exchange (BEI) period 2009-2016. The sample was chosen using purposive sampling method, with the number of 3 (three) companies during the period 2009-2016. Data analysis techniques use classical assumption test, multiple linear regression analysis and hypothesis test. This analysis is done by using SPSS 20 program. This research shows that the variable of asset structure, profitability and growth of company partially have no significant effect to capital structure, while simultaneously have low effect to capital structure.